2014
DOI: 10.4236/gep.2014.23014
|View full text |Cite
|
Sign up to set email alerts
|

Some Mass Migration Underground Found in Beijing Area

Abstract: The relationship between the change of a local gravity field and the mass migration underground is discussed by means of using a point-source disturbed body as a substitute for the mass migration underground. Some significant local gravity field changes in Beijing area have been found, from which the three parameters of the disturbed bodies, location, depth and mass, have been derived successfully from the observations of a gravimetric network. In order to determine the depth of a body, a new approach is sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Zheng et al found that the timing of the two pair local gravity field change (LGFC) can be attributed to two earthquakes in the Beijing region and a related underground mass migration of up to 20 km. The left two images are the local gravity field change (LGFC) before the earthquake near Beijing in 1998, and the right two images are the ones after the earthquake [11]. about 10 m s , 7 2 -which is two orders of magnitude smaller that what can be measured with the experiment presented here in its current setup.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Zheng et al found that the timing of the two pair local gravity field change (LGFC) can be attributed to two earthquakes in the Beijing region and a related underground mass migration of up to 20 km. The left two images are the local gravity field change (LGFC) before the earthquake near Beijing in 1998, and the right two images are the ones after the earthquake [11]. about 10 m s , 7 2 -which is two orders of magnitude smaller that what can be measured with the experiment presented here in its current setup.…”
Section: Resultsmentioning
confidence: 65%
“…It is interesting to see whether our experiment, if repeated in an undergraduate experimental program year after year, can reflect changes in gravity triggered by external local events. Zheng et al [11] discussed the relationship between the change of a local gravity field and the underground mass migration in the Beijing area by means of using a point-source disturbed body as a substitute for the mass migration underground ( figure 7). Zheng et al found that the timing of the two pair local gravity field change (LGFC) can be attributed to two earthquakes in the Beijing region and a related underground mass migration of up to 20 km.…”
Section: Resultsmentioning
confidence: 99%
“…The cultivation of public spirit needs to be gradually trained in specific situations, and become a natural way of thinking, attitude and even behaviour through long-term accumulation. [4] More importantly, it mobilises the intrinsic motivation of students to nurture themselves [5] . Therefore, it can be said that the pedagogy of participatory experiential learning is highly compatible with the shaping of public spirit.…”
Section: The Fitness Of Participatory Experiential Learning and The S...mentioning
confidence: 99%